2017
DOI: 10.1371/journal.pone.0179546
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patterns of adherence to medication therapy among patients with type 2 diabetes mellitus in Denmark: The importance of initiation

Abstract: AimsPoor adherence to medication therapy among type 2 diabetes patients is a clinical challenge. We aimed to determine which factors are associated with the three phases of long-term adherence to medication: initiation, implementation and discontinuation in a register-based study.MethodsAdherence to six medicine groups (metformin, sulfonylureas, acetylsalicylic acid, thiazide diuretics, renin angiotensin system inhibitors, and statins) were analysed among 5,232 patients with type 2 diabetes at a tertiary refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
1
10
2
1
Order By: Relevance
“…Zaslavsky et al (30) found a U-shaped relationship in the FG/HbA 1c -frailty interaction, with both extreme high and low levels associated with frailty. The cause of this U-shaped relationship is compliance with CVD medication increases when people with diabetes have more than one prescription (31). We did not find that FG was associated with frailty trajectories.…”
Section: Discussioncontrasting
confidence: 67%
“…Zaslavsky et al (30) found a U-shaped relationship in the FG/HbA 1c -frailty interaction, with both extreme high and low levels associated with frailty. The cause of this U-shaped relationship is compliance with CVD medication increases when people with diabetes have more than one prescription (31). We did not find that FG was associated with frailty trajectories.…”
Section: Discussioncontrasting
confidence: 67%
“… Mobile telemonitoring offers benefits for treating diabetes. Jensen et al (2017) 60 Denmark Understanding the risk factors of adherence reduction related to the different phases of treatment. Factors that can decrease adherence are different from the treatment phases.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, emergence and worsening of complications result in significant impact on physical, emotional and social aspects of life. Moreover, nonadherence to antidiabetic agents increases the risk for hospitalisation and all-cause mortality (Jensen, Jørgensen, Hansen, Aagaard, & Carstensen, 2017).…”
Section: Introductionmentioning
confidence: 99%